1994
DOI: 10.1159/000217118
|View full text |Cite
|
Sign up to set email alerts
|

Haemate P<sup>®</sup> in Children with von Willebrand’s Disease

Abstract: In our center, 289 children with von Willebrand’s disease (vWD) have been diagnosed since 1982. The majority of cases (n = 198) were congenital vWD whereas 91 patients suffered from vWD induced by valproate (VPA). We overview bleeding episodes in 45 children and 64 operative procedures requiring therapeutic intervention. The aim of therapeutic and prophylactic procedures in vWD is correcting the hemostatic disorder and normalization of bleeding time. This can be achieved by application of Haemate P leading to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 0 publications
3
54
0
Order By: Relevance
“…Improvement of the VWF multimer pattern in plasma, and the shortening of bleeding time, are important determinants of hemostatic capacity in the concentrates and cannot be described with ordinary pharmacokinetic variables. Furthermore, pharmacokinetic parameters such as half life, in-vivo recovery (IVR), and others, depend on the type of VWF concentrate; the recovery of FVIII:C, VWF:Ag, and VWF: RCo have been shown to differ markedly [9,11,13,15,16,[19][20][21][22][23][36][37][38]. Table 3 shows the pharmacokinetic parameters of selected concentrates.…”
Section: Pharmacokinetic Of Von Willebrand Factor/factor VIII Concentmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvement of the VWF multimer pattern in plasma, and the shortening of bleeding time, are important determinants of hemostatic capacity in the concentrates and cannot be described with ordinary pharmacokinetic variables. Furthermore, pharmacokinetic parameters such as half life, in-vivo recovery (IVR), and others, depend on the type of VWF concentrate; the recovery of FVIII:C, VWF:Ag, and VWF: RCo have been shown to differ markedly [9,11,13,15,16,[19][20][21][22][23][36][37][38]. Table 3 shows the pharmacokinetic parameters of selected concentrates.…”
Section: Pharmacokinetic Of Von Willebrand Factor/factor VIII Concentmentioning
confidence: 99%
“…Intermediate-purity and high-purity von Willebrand factor/factor VIII concentrates Substantial data have shown that VWF/FVIII concentrates are equally effective in attaining normal and sustained FVIII:C levels postinfusion, although peak levels are more delayed with concentrates devoid of FVIII:C [9,11,13,15,16,[19][20][21][22][23]35,37]. The intermediate-purity and high-purity VWF/FVIII concentrates contain large amounts of FVIII and VWF; high postinfusion levels of these moieties are consistently obtained.…”
Section: Very High Purity Factor VIII Concentratesmentioning
confidence: 99%
“…Therefore the recommendation to treat the mild quantitative defects, such as type 1 vWD, and a proportion of the qualitative defects, such as type 2A vWD, with DDAVP is widely accepted [7,10]. However, in rarely occurring defects and especially in type 2 de®ciencies many authors prefer replacement therapy with plasma products [1,3,5,11]. Although few reports have investigated the response of individual type 2M families to DDAVP in a test situation [2,6,8], to our knowledge nothing is known about the de®nite hemostatic eect in the clinical setting, such as oropharyngeal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly the bleeding time, an important determinant of the bleeding tendency in vWD, in type 2M patients might be borderline or prolonged. The common therapy of choice during operative interventions in rarely occurring subtypes of vWD has been proposed to be the transfusion of vWF/ FVIII plasma concentrates [1,3,5,11]. In this report, however, we describe for the ®rst time the feasibility of perioperative DDAVP administration in a child with vWD type 2M.…”
Section: Introductionmentioning
confidence: 90%
“…In the past, it has been recommended for major surgery in patients with type 3 VWD to infuse factor concentrates, such as Haemate P, with a bolus dose of 30± 40 IU/kg, followed by 15± 25 IU/kg every 12 h for 3 days and 15± 25 IU/kg daily for 3± 5 days [8]. Haemate P was also recommended at a dose ranging from 20 to 80 IU/kg every 12 h for periods ranging from 3 to 10 days, depending on the VWD type, the severity of the bleeding, or the type of surgery [9,10]. Continuous infusion of factor concentrates is a new and feasible procedure in situations requiring hemostatic control of pediatric and adult patients with VWD.…”
Section: Discussionmentioning
confidence: 99%